The Endothelial-Mesenchymal Transition (EndMT) and Tissue Regeneration - Yu, Wenjing; Liu, Zhen; An, Shu; Zhao, Jinyi; Xiao, Lan; Gou, Yongchao; Lin, Yunfeng; Wang, Jun (Current Stem Cell Research & Therapy, 2014)
Recent studies have brought endothelial-mesenchymal transition (EndMT) as a special perspective of epithelial- mesenchymal transition (EMT) into eyes. Traditionally, EndMT is considered as a source for fibroblasts and myofibroblasts, and it is extensively investigated in physiologic cardiac development as well as in pathologic tumor and fibrosis. Recently, new studies have found that EndMT-transformed cells had ‘stemness’, which means they could differentiate into chondroblasts, osteoblasts, and adipoblasts in differential culture, respectively. This gives EndMT a bright application future in tissue engineering and regeneration, especially for the formation of cartilage and bone.
Keywords: EndMTtransformed cells